Gigi Tiruan Kaitan Presisi untuk Kasus Unilateral Free End Rahang Bawah - Laura Susanti Himawan (Faculty of Dentistry, Universitas Indonesia, 2015)
It is not easy to find a good and comfortable design for a lower unilateral free end denture (Class II Kennedy), while a fixed bridge is contraindicated, and removable denture is not convenient, because a bar is esxisting on the floor of the mouth. The latest and most sophisticated way is to construct an implant supported denture, but this method is not preferred by most of the patients because surgery has to be undergone. To solve this problem, a precision attachment denture with an extracoronal retainer using MKI hinge attachment was used. The female part of the attachment was placed distal of tooth 45, and tooth 44 and 45 were splinted together , then a removable saddle denture was fabricated for the missing tooth 46. Patient female, aged 50 years very pleased with her denture because it fulfilled her expectation. MKI hinge attachment for a lower unilateral free end denture gives good result in function as well as esthetic.